Revision and psychometric evaluation of a fertility intention scale for young women with breast cancer in Chinese Mainland - Fei Zhu; Chunlei Liu; Queting Chen; Wanmin Qiang; Qian Lu (Elsevier, 2023)
Objective: Neglected fertility intentions affect the quality of life of young women with breast cancer. The purpose of this study was to revise the Taiwanese version of the Fertility Intention Scale and validate its psychometric properties among young women with breast cancer in Chinese Mainland. Methods: We performed a cross-sectional survey with young women with breast cancer at a Chinese cancer hospital to evaluate the psychometric properties of the Revised Fertility Intention Scale. A two-phase study was conducted: (1) revision of the scale and (2) evaluation of the scale's reliability and validity. Results: Six new items and one new dimension were added to the original 15 items and four dimensions, reliability and validity of the 21-item Revised Fertility Intention Scale were verified in a sample of 436 women in Chineses Mainland with breast cancer who were aged 18-40 years. The content validity index, results of factor analysis, convergent validity, and known-groups validity were acceptable, and the Cronbach's alpha and intraclass correlation coefficients supported the revised scale. Conclusions: The 21-item Revised Fertility Intention Scale has satisfactory reliability and validity for assessing fertility intentions among young women with breast cancer in Chinese Mainland. In clinical practice, nurses can use the scale to identify fertility intentions and associated factors in young women with breast cancer and develop feasible and effective oncofertility care measures.